The Chinese Media Effect in Bull and Bear Markets. Issue 3 (3rd July 2019) - Huang, Tzu-Lun
Abstract: Current studies on the media effect fail to reach a consistent conclusion in a global setting. Lacking independence and highly controlled, the media functions differently in China and exerts unexpected influences on capital markets. Focusing on listed companies in China, the author analyzes the media effect on stock returns and further considers market states. Using a comprehensive database on firm-related news stories, stocks with high media coverage are found to possess higher stock returns, Jensen's alphas, and Daniel et al. [1997 ] adjusted returns over the 2007–2014 sample period. Moreover, the media effect is stronger in bull markets than in bear markets. The result is robust to model settings, alternative definitions of market states, estimation methods, portfolio formation, and sample selection. The study contributes to the literature by advancing the understanding of the Chinese media effect in bull and bear markets.